2021
DOI: 10.1210/endocr/bqab183
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of OCT4 on 3,5,3’-Tri-iodothyronine and FSH-induced Granulosa Cell Development in Female Mice

Abstract: Octamer-binding transcription factor 4 (OCT4) regulates the pluripotency of stem cells and also plays important roles in granulosa cells growth, which is regulated by follicle-stimulating hormone (FSH). Thyroid hormone (TH) is important for the development and maturation of follicles and the maintenance of various endocrine functions. Although 3,5,3′-triiodothyronine (T3) enhances the effects of FSH on the regulation of the growth of granulosa cells and development of follicles, it is unclear whether and how T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…And OCT4 not only promotes the formation of stem cells and germ cells, but also increases granulosa cell development (56). In our previous study, the expression of OCT4 is regulated by ERβ and CYP51, which are related to the synthesis and effects of estrogen (7). In the present study, omega-3 down-regulated OCT4 expression.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…And OCT4 not only promotes the formation of stem cells and germ cells, but also increases granulosa cell development (56). In our previous study, the expression of OCT4 is regulated by ERβ and CYP51, which are related to the synthesis and effects of estrogen (7). In the present study, omega-3 down-regulated OCT4 expression.…”
Section: Discussionsupporting
confidence: 65%
“…The hydrophilic molecule glucose cannot permeate the cell membrane, and its utilization requires the transport and catalysis of GLUTs, which is a protein family, including a variety of proteins, widely distributed in various tissues in the body (7,(30)(31)(32). In this study, we showed that omega-3 significantly down-regulated GLUT1 and GLUT4 proteins content.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Within the ovary, granulosa cells proliferate in the developing follicle during folliculogenesis and are regulated by a variety of factors (e.g. follicle stimulating hormone, thyroid hormone, oestrogen, octamer binding transcription factor 4 [OCT4]; Wang et al, 2021;Yada et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The accelerated metabolic rates and the cumulative accumulation of the reactive oxygen species (ROS) are linked to higher demands for energy and nutrients throughout the reproductive process. Unfavorable environmental conditions, such as bacterial infection and heat stress, are well known to promote the accumulation of ROS [22,37]. Although ROS are by-products of aerobic metabolism that are naturally occurring, the excessive ROS production causes oxidative stress and cellular damage.…”
Section: Discussionmentioning
confidence: 99%